THE EFFECTS OF PRE-QUESTIONING AND STUDENTS PERCEPTION ON TEACHING MEDIA TOWARDS STUDENTS READING COMPREHENSION - Tri Angkarini (Scope : Journal of English Language Teaching, 2020)
The objective of this study was to investigate the effect of pre-questioning and students perception on teaching media towards students’ reading comprehension in private vocational high school Tangerang. The students were in the relevant grade (second grade) during a period of three months in which this study was conducted. The writer used survey method in this study. Data collection were conducted by taking the test and distributing questionnaires. The data were processed and analyzed by using statistic descriptive, normality test, linearity test, Multicorrineality test, and hypotheses test. Statistic test uses t test and F test. The research shows that there is an effect of students pre-questioning and students perception on teaching media altogether towards reading comprehension with the regression analisis:  = 34,89 + 0,408  X1 – 0.056 X2. Whenever there is a rise in the value of pre-questioning, there will be a rise in the level of students’ reading comprehension of 0,408 and whenever there is an increase in the value of students perception on teaching media, there will be a decrease in students’ reading comprehension for 0,056.